PENGATURAN DAN PERLINDUNGAN HAM DALAM UUD 1945 SERTA ASPEK PIDANA NASIONAL DAN INTERNASIONAL - Lisnawaty Badu (Universitas Negeri Gorontalo, 2010)
Developments in society requires the recognition of human rights as the most fundamental rights. Understanding human rights, as well as the related liability so between the two are inseparable. Obligations contemplated in this paper is none other than the regulation and protection of human rights in the Constitution of 1945 and the Indonesian criminal law. One thing is for sure that human rights have a primary position and the first in living in a society, because the existence of rights inherent in its nature has been since the birth of the human person. Reality shows that human rights in Indonesia is always a highlight sharp and continuous conversation material, either because the basic concept derived from the Constitution in 1945 and its practical realities on the ground full of violations. The emergence of various cases of human rights abuses has spawned a collective consciousness about the need for regulation and protection of human rights through legal instruments such as the basic law and legislation such as criminal law. Keywords: Protection, Human Rights, UUD 1945, Criminal Law.